BOOK REVIEW: The Book of Beetles. A lifesize guide to six hundred of nature’s gems (editd by Patrice Bouchard, Ivy Press, UK, 2014, 656 pages) - Čiampor, Fedor Jr. (Zootaxa, 2015)
Today, there are plenty of beetle books available on the market. They usually introduce readers to the biggest or smallest, strangely-shaped, or markedly-coloured beetle species. This generally proves to be fairly easy given the richness of morphological and ecological diversity within this order. Unfortunately, such treatments only capture a fraction of the world‘s Coleoptera diversity, use the same examples, and sometimes even the same pictures. That is almost all you learn about one of the biggest and most important animal groups in the world. The Book of Beetles (BoB) does not focus on any of the usual attributes, i.e., biggest size, most shining body or the longest nose. In spite of this (or maybe because of it), the BoB is exceptional.